Synthesis, characterizations, crystal structure and anticancer activity of Mn(II), Co(II) and Ni(II) complexes of N′-cyclohexyl-2-thiophene-carbonyl hydrazine carbothioamide. (1st July 2023) - Jaiswal, Shubham; Yadav, Lokesh; Kumar Pandey, Shivendra; Chandra, Suryansh; Bharty, M.K.; Prasad, L.B.; Acharya, A.
Graphical abstract: Here, the crystal structures and spectroscopic characterizations of three metal complexes [Mn(tach)2 ( o -phen)] (1), [Co(tach)2 ( o -phen)] (2), [Ni(tach)2 ( o -phen)] (3 ) with thiosemicarbazide derived N -cyclohexyl-2-thiophene-carbonyl hydrazine carbothioamide (Htach) ligand is reported. The anti-cancer study of ligand and its complexes were evaluated against Dalton's lymphoma (DL) cancer cell lines through MTT, AO/EtBr and DAPI based assays. Our investigation suggested that metal–ligand complexes have significant strong anticancer activity against tumour cells in a dose-dependent manner. The IC50 values for ligand and its metal complexes 1 –3 were found as 20, 10, 20 and 5 µM, respectively. Abstract: The current century has witnessed continuous and exponential increase in the number of patients suffering from different types of sarcomas. To cure these sarcomas, there are continuous efforts to develop more efficient and less cytotoxic anti-cancerous and antitumor drugs. A thiosemicarbazide derived N -cyclohexyl-2-thiophene-carbonyl hydrazine carbothioamide (Htach) and its metal complexes [Mn(tach)2 ( o -phen)] (1 ), [Co(tach)2 ( o -phen)] (2 ), [Ni(tach)2 ( o -phen)] (3 ) were synthesized and reported here. In these complexes, o -phen was used as secondary ligand for coordinatively saturation of metal ions. The synthesized ligand and complexes are well characterized with different elemental analysis FT-IR, and UV–visible and HR-MS spectroscopy. Further, Complex 1 was characterized by single XRD and crystallized in monoclinic system with space group P 21 /n. The anti-proliferative potential of ligand and its complexes were evaluated against Dalton's lymphoma (DL) cancer cell lines through MTT, AO/EtBr and DAPI based assays. The effect of these metal complexes on normal cell lines (splenocyte) has been also investigated. Our investigation reveals that metal–ligand complexes have significant strong anticancer activity against tumor cells in a dose-dependent mode, whereas minimal effect on normal cell lines. For ligand and complexes 1 –3, the IC50 values were found as 20, 10, 20 and 5 µM, respectively. These results suggest that among Mn, Co and Ni complexes, nickel complex will be more effective for the functionalization of anticancer agents.